PERTUMBUHAN OKULASI JERUK KEPROK BRASTEPU (Citrus nobilis Var. Brastepu) MENGGUNAKAN JERUK ASAM SEBAGAI BA TANG BA WAH - Nurwahyuni, Isnaini; Napitupulu, Justin A; ., Rosmayati; Harahap, Fauziah (JURNAL PENELITIAN SAINTIKA, 2012)
The growth of Citrus nobilis Var. Brastepu budding that is free fromCitrus Vein Phloem Degeneration (CVPD) is explained. The method is conductedby taking of bud stick from a selected healthy citrus Brastepu plant and is thengrafted into a sour orange (Citrus auraniium) as mother trees via budding method.The research is conduted in Desa Bukit, Brastagi North Sumatra, Indonesia.Optimum conditions on the budding technique have been obtained to produce goodqualih; seedling of Citrus nobilis Var. Brastepu. Growth characteristics of the plantin various treatment conditions have been studied based on the growth leaves, stem,and branches. Analysis of the DNA using RAPD-PCR method has confirmed thatall new seedling produced in the propagation method are free from CVPD.